59‐4: Reduction of Possible Flicker and Color Breakup using Deflicker‐FSC Method for Field‐Sequential‐Color Displays. Issue 1 (May 2016) - Teng, Kai‐Tung; Lin, Fang‐Cheng; Chang, Chi‐Wen; Lin, Ching‐Huan; Huang, Yi‐Pai; Shieh, Han‐Ping D.
Abstract : This paper proposes a driving method for 240Hz field‐sequential‐color displays. The proposed method redistributes the image energy in the displayed color fields with the modulation of backlight and liquid crystal signals. Most of the image luminance was concentrated in two multicolor fields, while the luminance of the other mono‐color fields was much reduced. The proposed driving method can not only avoid the potential flicker issue but suppress the color breakup phenomenon.